Stability Analysis of nth Order Nonlinear Impulsive Differential Equations in Quasi–Banach Space. (17th February 2020) - Zada, Akbar; Mashal, Asia
Abstract: This article is about Ulam's type stability of n th order nonlinear differential equations with fractional integrable impulses. It is a best procession to the stability of higher order fractional integrable impulsive differential equations in quasi–normed Banach space. Different Ulam's type stability results are obtained by using the definitions of Riemann–Liouville fractional integral, Hölder's inequality and the beta integral inequality.